MEDIA GAMBAR PHOTOGRAPHY DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Rusiadi (CV. ADIBA ASIHA AMIRA, 2026)
Learning media is an essential component in the educational process that functions as an intermediary in delivering messages or information from educators to learners. This article aims to examine the classification and types of learning media based on their characteristics, forms, and technological developments. Learning media can be classified from several perspectives, including sensory involvement (audio, visual, and audiovisual), technology-based categories (traditional media and digital-based media), and usage methods (projected) Photography is a visual medium that plays a vital role in the learning process. Etymologically, photography comes from the Greek words photos (light) and graphos (image), meaning the process of drawing with the aid of light. In an educational context, photographic images serve as a learning medium capable of presenting objects in a concrete, realistic, and easily understood manner by students. This study aims to examine the definition of photographic images, selection criteria, principles of use, advantages and disadvantages, and production techniques for learning. The method used was library research, analyzing various sources related to photography as a learning medium. The results of the study indicate that the appropriate use of photographic images can enhance student understanding, particularly in explaining abstract concepts more concretely. However, their use must still consider pedagogical and technical criteria to be effective.